Pembuatan Film Dokumenter tentang Pengaruh Pestisida dalam Pertanian Kentang Desa Pandansari, Brebes, Jawa Tengah - Dari, Nur Wulan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
Pandansari Village, Brebes District, Central Java, which is located at an altitude of 1.500-2.000 meters above sea level, the majority of its residents work in the plantation sector as well as farming vegetable commodities, especially potatoes. Environmental changes, especially climate, such as high levels of rainfall can cause the presence of pests and viruses, thus making farmers think more about preventing crop failure. Pesticides are often used to keep plants producing. However, high-scale use of pesticides can have negative impacts, especially on health. Research – Community Service uses a focused discussion forum approach, interviews, and participatory documentary filmmaking with the community to understand the influence of pesticides on potato farming. The positive and negative effects of pesticides on potato farming in Pandansari Village are shown through a documentary entitled,